Perlindungan Hukum terhadap Konsumen dalam Pembelian Produk Thrifting Impor di Indonesia - Laura Aulia Rosaline; Asa Diamon; Zaki Ardiansyah; Sintong Arion Hutapea (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
This study aims to determine the extent to which the Consumer Protection Law in Indonesia can provide effective protection to consumers who buy imported thrifting products that are prohibited under the trade ministerial regulation and whether the difference in legality status between local and imported thrifting affects the level of consumer protection in terms of quality and safety. The research method used is the Normative method which refers to Law Number 8 of 1999 concerning Consumer Protection, Law Number 7 of 2014 concerning Trade / Government Regulation in Lieu of Law concerning Job Creation, and Regulation of the Minister of Trade Number 40 of 2022 concerning Amendments to Regulation of the Minister of Trade Number 18 of 2021 concerning Prohibited Export Goods and Prohibited Import Goods. The results of the study show that the buying and selling of local thrift clothing is allowed and not against the law. The reason the government prohibits the importation of used clothing is to protect the local textile industry and protect consumers from risks that endanger skin health. Therefore, if consumers know about and continue to buy imported thrift clothing, then these consumers cannot get legal protection even though the Consumer Protection Law guarantees consumer rights.